Correlates of pediculosis preventive behaviors among female adolescents using a theoretical framework: A case of health belief model - Masumeh Naseri; Mohtasham Ghaffari; Sakineh Rakhshanderou (Journal of Education and Health Promotion)
BACKGROUND: Despite improving health levels, not only in developing countries but also in developed countries, pediculosis is still a threat to public health and a health problem. The aim of this study was to investigate the factors related to preventive behaviors of head lice infection in adolescent girls using a health belief model (HBM). MATERIALS AND METHODS: The present study is a descriptive-analytical which was performed on 600 fourth-, fifth-, and sixth-grade female students in Shahroud by multi-stage sampling method. The data collection tool was a questionnaire in which validity and reliability were confirmed. Data were analyzed using descriptive tests including frequency distribution tables and analytical statistics using Pearson and Kendall correlation coefficient tests and multiple regression. RESULTS: There was a significant positive correlation between head lice prevention behaviors in students and perceived awareness, severity, benefits, and self-efficacy. Also, the variables of perceived barriers and benefits from the constructs of HBM and mothers’ age and education were identified as the final predictors of behavior. CONCLUSION: Based on the HBM, perceived benefit structures and perceived barriers had the most impact on head lice prevention behavior in students. It is suggested that in designing educational interventions, the structures of perceived benefits and perceived barriers be emphasized as the most important behavioral predictors in the prevention of head lice infection in students. It is also strongly recommended that mothers be educated in this area.